The long-run effects of conditional cash transfers: the case of Bolsa Familia in Brazil - Laguinge, Luis Alberto (2024)
Conditional Cash Transfers (CCTs) have become a key antipoverty policy in Latin America in the last 25 years. The ultimate goal of this kind of programs is to break the intergenerational transmission of poverty through the promotion of human capital accumulation of children in vulnerable households. In this paper, we explore this issue by estimating the long-run effects of the largest CCT in Latin America: the Brazilian Bolsa Familia. Through a combination of the two-stage-two-sample method and a difference-in-differences approach, we find evidence consistent with a positive long-run impact of Bolsa Familia among former beneficiaries. In particular, we find a significant positive effect on education and labor income, and a negative effect on the likelihood of being a current beneficiary of this social transfer.